1986
DOI: 10.1159/000132300
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved early replicating segment on the sex chromosomes of man and the great apes

Abstract: Replication studies on prometaphase chromosomes of man, the chimpanzee, the pygmy chimpanzee, the gorilla, and the orangutan reveal great interspecific homologies between the autosomes. The early replicating X chromosomes clearly show a high degree of conservation of both the pattern and the time course of replication. An early replicating segment on the short arm of the X chromosomes of man (Xp22.3) which escapes inactivation can be found on the X chromosomes of the great apes as well. Furthermore, the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…This segment appears, therefore, to be the most invariant part of the higher primate Y chromosome, whereas other euchromalic parts have undergone important rearrangements, in addition to the spreading or complete disappearance of heterochromatic regions (Weber et al, 1986). Deletion map ping studies in man have shown that the testis-dclcrmining factor (TDF) maps to the distal short arm, proximal to the pscudoautosomal region (Vergnaud ct al.. 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This segment appears, therefore, to be the most invariant part of the higher primate Y chromosome, whereas other euchromalic parts have undergone important rearrangements, in addition to the spreading or complete disappearance of heterochromatic regions (Weber et al, 1986). Deletion map ping studies in man have shown that the testis-dclcrmining factor (TDF) maps to the distal short arm, proximal to the pscudoautosomal region (Vergnaud ct al.. 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It may well turn out to be, when more species have been examined, that XY pairing regions universally will be found to share these common properties. Data already exist showing that the early replicating band Xp22.3 in the pseudoautosomal region of the human X chromosome is also early replicating in several primate species and shows functional homology with the most early replicating band on the Y (Weber et al, 1986a). In situ hybri disation of human-derived pseudoautosoma!…”
Section: Discussionmentioning
confidence: 99%
“…Eutherian X and Y chromosomes recombine only at the so-called pseudoautosomal region (PAR), which is located at the tip of one arm of X and Y chromosome, respectively (Gläser et al, , 1999Toder et al, 1997). While the X chromosome seems to be highly conserved throughout the eutherian orders, the Y chromosomes show a broad spectrum of species-specific morphological divergence (Weber et al, 1986;Schempp et al, 1989;Müller, 1993). Indeed, the Y chromosomes of various higher primate species exhibit a wide range of structural rearrangements including enormous differences in the degree of amplification of gene family members within their non-recombining regions (NRYs) (Schempp et al, 1995;Gläser et al, 1998;Wimmer et al, 2002a).…”
Section: Copyright © 2005 S Karger Ag Baselmentioning
confidence: 99%